An analysis of bacteriuria rates after endourological procedures. Issue 1 (3rd August 2022) - Seenappa, Nethravathy Billava; Sinha, Maneesh; Krishna Prasad, Thyagaraj; Krishnamoorthy, Venkatesh
Abstract: Medical literature on infection rates for certain specific endourological procedures is available. However, literature is lacking in providing a comprehensive view of the overall post endoscopic infection rates and their risk factors. This article attempts to provide an understanding of overall bacteriuria rate and discuss the contributory factors for common endourological procedures performed in a dedicated urology unit. This was a retrospective analysis of all patients who underwent endourological procedures at our Institute between January 2019 and December 2019. The following factors were assessed as contributors to post‐operative bacteriuria: gluteraldehyde versus plasma sterilization of endoscopic equipments, elective versus emergency procedures, age group, the presence of pre‐operative foreign bodies, post‐operative stent, chronic kidney disease (CKD), diabetes mellitus (DM), procedure time and American Society of Anaesthesiology (ASA) grades. The overall post‐operative bacteriuria rate was 17.85% in our total study population, 6.37% had symptomatic urinary tract infection (UTI). Chronic kidney disease (OR 3.5, p < 0.003) and higher ASA grade (OR 1.92, P < 0.002) appear to confer the highest risk of bacteriuria. The factors which were associated with a trend towards a higher incidence of UTI without reaching statistical significance included: the use of gluteraldehyde versus plasma sterilization, pre‐operative implants (Foley and ureteric stents), diabetes, advanced age, endoscopy time, post‐operative stent emergency surgeries and a clinical decision against the use of prophylactic antibiotics. The overall rate of bacteriuria in all endourological procedures was 17.8%, 6.37% had symptomatic UTI. Chronic kidney disease and higher ASA grades were the most important contributing factors to develop post‐operative bacteriuria.